Simultaneous Control of Staphylococcus aureus and Bacillus cereus Using a Hybrid Endolysin LysB4EAD-LysSA11 - Bokyung Son (Antibiotics, 2020)
Bacteriophage endolysins have attracted attention as promising alternatives to antibiotics, and their modular structure facilitates endolysin engineering to develop novel endolysins with enhanced versatility. Here, we constructed hybrid proteins consisting of two different endolysins for simultaneous control of two critical foodborne pathogens, Staphylococcus aureus and Bacillus cereus. The full-length or enzymatically active domain (EAD) of LysB4, an endolysin from the B. cereus-infecting phage B4, was fused to LysSA11, an endolysin of the S. aureus-infecting phage SA11, via a helical linker in both orientations. The hybrid proteins maintained the lytic activity of their parental endolysins against both S. aureus and B. cereus, but they showed an extended antimicrobial spectrum. Among them, the EAD of LysB4 fused with LysSA11 (LysB4EAD-LyaSA11) showed significantly increased thermal stability compared to its parental endolysins. LysB4EAD-LysSA11 exhibited high lytic activity at pH 8.0–9.0 against S. aureus and at pH 5.0–10.0 against B. cereus, but the lytic activity of the protein decreased in the presence of NaCl. In boiled rice, treatment with 3.0 µM of LysB4EAD-LysSA11 reduced the number of S. aureus and B. cereus to undetectable levels within 2 h and also showed superior antimicrobial activity to LyB4EAD and LysSA11 in combination. These results suggest that LysB4EAD-LysSA11 could be a potent antimicrobial agent for simultaneous control of S. aureus and B. cereus.